Development of a TikTok Filter-Based Quiz for Learning German Articles among Students in the German Language Education Study Program at Universitas Negeri Malang - Najla Esa Syahirah; Deddy Kurniawan (Universitas Negeri Malang, 2026)
This study aims to develop an interactive learning medium in the form of a TikTok filter-based quiz to support A1-level German language learning. The study employed the ADDIE development model, and the product was created using the Effect House application with a head-tracking feature that allows users to answer questions by moving their heads. The validation process involved media and subject matter experts, both of whom rated the product as highly feasible. A limited pilot test involving 22 students from the German Language Education Study Program, Universitas Negeri Malang, yielded highly positive responses, with over 95% approval across indicators such as clarity, attractiveness, and educational value. These findings indicate that TikTok filter-based quizzes with interactive features can serve as effective and engaging learning media for digital-native learners.